The Effect of Wordwall-Assisted Problem-Based Learning Model on Improving Mathematical Literacy and Self-Regulated Learning - Nuraeni Nuraeni; Hamidah Hamidah; Sarah Caesarani; Jaka Wijaya Kusuma (Nindikayla Institute, 2025)
This study aims to determine the improvement of students' mathematical literacy skills given learning with a problem-based learning model assisted by Wordwall is better than those using conventional learning. This study uses a quantitative approach with a quasi-experimental design type Pretest-Posttest Control Group Design. The research subjects consisted of 32 students of class VII D as the experimental class and 32 students of class VII B as the control class at SMP Negeri 16 Kota Serang. The instruments used were essay tests to measure mathematical literacy and Likert scale questionnaires to measure self-regulated learning. The results of the analysis showed that the average N-Gain of the experimental class was 66.51 and the control class was 38.81. The t-test showed a sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the two groups. The average score of the self-regulated learning questionnaire in the experimental class reached 80%. This study concluded that the use of the PBL model assisted by Wordwall is more effective in improving students' mathematical literacy and self-regulated learning compared to conventional learning.